Efficacy of a Homeopathic Medicine of Capsicum frutescens L. (Solanaceae) in the Treatment of Hot Flashes in Menopausal Women: A Phase-2 Randomized Controlled Trial - Andrade, Débora Cristiane da Silva; Carmona, Fabio; Angelucci, Mateus Andrea; Martinez, Edson Zangiacomi; Pereira, Ana Maria Soares (Homeopathy, 2019)
Background Hot flashes are common in women during menopause, and are an important cause of discomfort, increasing the number of medical appointments. Hormone replacement therapy is an effective treatment, but it can bring undesirable consequences. Alternative treatments exist but they are not universally accepted or effective. The ingestion of malagueta peppers (popular name for fruits of Capsicum frutescens L., Solanaceae) causes sensations similar to those experienced by women during hot flashes. Using the homeopathic law of similars (let like be cured by like), we hypothesized that a homeopathic remedy made of malagueta peppers can be effective in alleviating menopausal hot flashes. We named this remedy Malagueta.Methods This randomized, placebo-controlled, double-blind, phase-2 clinical trial was designed to test the hypothesis that, in menopausal women, the homeopathic medicine Malagueta (30 CH), compared with placebo, will significantly reduce the intensity of hot flashes, after 4 weeks of treatment. The primary outcome was the intensity of hot flashes, measured by the Measure Yourself Medical Outcome Profile (MYMOP) instrument. A total of 40 women were enrolled in the study, 20 in each group.Results The effect of Malagueta on the primary outcome, the intensity of hot flashes, assessed by MYMOP, was superior to that of placebo over the 4 weeks of treatment, with worsening in both groups after treatment was interrupted (after week 4, p < 0.001 in ordinal logistic regression). The odds ratio for treatment response (reduction of at least three MYMOP categories) was 2.78 (95% confidence interval, 0.77 to 10.05). Treatment with Malagueta, compared with placebo, also reduced the intensity of the secondary symptoms (p = 0.001) and improved level of activity (p = 0.025) and well-being (p = 0.008).Conclusion The homeopathic medicine of Capsicum frutescens (Malagueta) was superior to placebo in reducing the intensity of hot flashes in menopausal women after 4 weeks of treatment.
Keywords: menopause; hot flashes; pepper; Solanaceae; homeopathy